Organizational Climate as Predictor of Happiness in Male and Female MNC Managers - Yadav D,; S.S. Sarangdevot, (International Journal of Scientific Research in Science and Technology, 2024)
Responsibility, work and task orientation, social relations, communication and information, resources, objectives, quality of working life, leadership, approach and method, autonomy are some of the factors of organizational climate. Knowing how or whether these factors predict happiness in multinational corporate managers, with respect to gender was the research question in the current study. The organizational climate—which encompasses: Stakeholder perspective with factors such as; role clarity, respect, communication, reward system, career development, planning and decision making, innovation, relationship, teamwork and support, job quality, conflict, commitment and morale, training and learning and direction which was perceived to have a strong relationship with happiness. It was also anticipated that organizational culture would be a strong indicator of MNC managers' satisfaction, both male and female. One hundred and fifty male and female MNC managers with at least ten years of work experience were selected from the National Capital Region (NCR) of Delhi, which comprises the cities of Jaipur City in Rajasthan State as well as Gurugram, Noida, and Ghaziabad. The Oxford Happiness Questionnaire (OHQ) (Hills and Argyle, 2002) and the Organizational Climate Questionnaire (OCQ) (Furnham, A. and Goodstein, L.D. 1997) completed by the male and female managers of MNCs. The method of correlational research and multiple regression analysis were applied. Research evidence also corroborated the results which reveal a significantly negative correlation of role clarity, reward system, career development, planning and decision making, conflict handling, training and learning and direction with happiness and a significantly positive correlation with respect, communication, relations, team work and support, quality of service, commitment, morale and happiness among both male and female MNC managers. Studies have repeatedly shown and confirmed that elements of organizational climate While direction and incentive systems are significant negative predictors of happiness for organizational climate elements, commitment and morale are significant positive drivers of happiness for both male and female managers of multinational corporations. The results are analyzed in light of recent empirical research.
Keywords: Organizational Climate; Happiness; Male and Female MNC Managers